1970
DOI: 10.3329/bmj.v40i1.9966
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Physical Illnesses: an Update

Abstract: Many chronic illnesses have a strong effect on an individual's mental and emotional status, and, in turn, undiagnosed mental disorders can affect a person's ability to cope with an illness and participate in the treatment and recovery process. Depression is the most common complication of almost all chronic or serious medical conditions. Major depression among persons experiencing chronic medical conditions like cardiovascular diseases, diabetes, respiratory diseases, obesity, cancer etc. increases the burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The only nationally representative survey conducted between 2003 and 2005 illustrated the high burden of mental disorders in Bangladesh (14). Notedly, mental health services are virtually non-existent at the primary care level throughout the country (15,16). There is a considerable lack of an adequate number of psychiatrists, and they are mostly located in big cities which makes the burden heavier (17).…”
Section: Introductionmentioning
confidence: 99%
“…The only nationally representative survey conducted between 2003 and 2005 illustrated the high burden of mental disorders in Bangladesh (14). Notedly, mental health services are virtually non-existent at the primary care level throughout the country (15,16). There is a considerable lack of an adequate number of psychiatrists, and they are mostly located in big cities which makes the burden heavier (17).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of major depression varies from 2.6% to 5.5% among males and from 6.0% to 11.8% among females (Dubovsky & Dubovsky, 2002). A recent Canadian analysis using data from the National Public Health Survey has found that among young adults ( aged 12 to 25 years) the highest rates of the first occurrence of depression (1.4% -9.1% of the public), and among those 65 years of age (1.3% -1.8%) are lower (Patten, 2000;Mohit, Maruf, Ahmed & Alam, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3 well as sympathovagal balance which represents interaction between cardiac sympathetic and parasympathetic activity 6 .…”
Section: Introductionmentioning
confidence: 99%